2017
DOI: 10.7196/ajhpe.2017.v9i3.786
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate trainees’ perceptions of the learning environment in a Nigerian teaching hospital

Abstract: Currently, progress report forms are completed annually by the trainers, i.e. specialist physicians and surgeons in the various teaching hospitals, to assess the progress of postgraduate training of junior doctors. At regular intervals, the colleges visit these hospitals to assess the facilities for postgraduate training for the purpose of maintaining the standard of training and re-accreditation of the institution for continued training of junior doctors. The term junior doctor in this regard refers to all ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…In a study by Idon et al . [ 14 ] on the perceptions of dental students on the educational environment in a new dental school in Maiduguri, Nigeria, the total mean DREEM score was 138.2/200 which is higher than that of this study. This could be due to the fact that the dental school is still new with new functional facilities.…”
Section: Discussioncontrasting
confidence: 80%
“…In a study by Idon et al . [ 14 ] on the perceptions of dental students on the educational environment in a new dental school in Maiduguri, Nigeria, the total mean DREEM score was 138.2/200 which is higher than that of this study. This could be due to the fact that the dental school is still new with new functional facilities.…”
Section: Discussioncontrasting
confidence: 80%
“…16 The medical and educational literature has shown that the quality of the educational environment plays a role in effective learning, 16 quality training 7,8 career satisfaction, 17,18 academic achievements, 18,19 burnout rates, 20 and the levels of engagement and motivation. [21][22][23] Anaesthesiology registrars spend most of their time in theatre, and this is a unique educational environment in which most of their training occurs. The ATEEM is a specific instrument for the measurement of the anaesthetic theatre educational environment.…”
Section: Methodsmentioning
confidence: 99%
“…Progress report forms are completed annually by the trainers to assess the progress of postgraduate training of surgical residents. However, feedback from trainee is usually sought when the colleges visit these hospitals for accreditation or re‐accreditation of the institution for continued postgraduate training [14].…”
Section: Introductionmentioning
confidence: 99%